PENGEMBANGAN MODEL ASESMEN BERBASIS KARAKTER UNTUK MENINGKATKAN NILAI-NILAI RELIGIUS PADA SISWA - Safitriana, Dian Ika (Universitas Tanjungpura, 2025)
Character education is essential in shaping students to be not only intellectually capable but also morally and spiritually mature. In Indonesia, religious values are a central component of national education, as outlined in Law No. 20 of 2003, which emphasizes nurturing students to be believers, devoted to God, and of noble character. The Merdeka Curriculum reinforces this by placing